2004
DOI: 10.1001/jama.291.23.2856
|View full text |Cite
|
Sign up to set email alerts
|

Travel Medicine Considerations for North American Immigrants Visiting Friends and Relatives

Abstract: RAVEL MEDICINE TRADITIONally focuses on assisting tourist and business travelers avoid travel-related illnesses. It is now clear that immigrants returning to their home countries, termed visiting friends and relatives (VFRs), are at particularly high risk and that traditional travel services are inadequate for protecting this population. This article will review existing data concerning the increased risk and discuss practical recommendations that may assist the primary care and travel clinicians.International… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
121
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(123 citation statements)
references
References 65 publications
1
121
0
1
Order By: Relevance
“…Adults likely to be immune because of previous exposure to HAV ask less frequently for pretravel health advice before traveling with their nonimmune Swiss-born children to their high-risk countries of origin. Often they visit areas outside usual tourist routes and have a longer duration of stay, including closer contacts to the local population [22][23][24]. As shown by the multivariate analysis, the patients who had traveled to visit friends or relatives were younger than those with HAV acquired in Switzerland; their infections occurred more often in the summer months, the usual vacation time of those visiting friends and relatives; and exposure to contaminated food was less frequently reported (data not shown), which may indicate a decreased awareness of exposure risks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adults likely to be immune because of previous exposure to HAV ask less frequently for pretravel health advice before traveling with their nonimmune Swiss-born children to their high-risk countries of origin. Often they visit areas outside usual tourist routes and have a longer duration of stay, including closer contacts to the local population [22][23][24]. As shown by the multivariate analysis, the patients who had traveled to visit friends or relatives were younger than those with HAV acquired in Switzerland; their infections occurred more often in the summer months, the usual vacation time of those visiting friends and relatives; and exposure to contaminated food was less frequently reported (data not shown), which may indicate a decreased awareness of exposure risks.…”
Section: Discussionmentioning
confidence: 99%
“…We should focus on the risk perceptions of travelers, such as those visiting friends and relatives and those going to popular destinations. Thus, through addressing hepatitis A risk among those visiting friends and relatives, we would not only protect individuals but may also potentially disrupt the transmission cycle in communities abroad and back home [22,36]. Targeted routine HAV vaccination of at-risk groups could be effective, as was shown with HAV vaccination of children of Turkish and Moroccan origin in Amsterdam [37].…”
Section: Discussionmentioning
confidence: 99%
“…4 Poor access to pretravel advice has been particularly asserted for VFR travelers, because of barriers at the health system level (eg, low insurance coverage rates), individual patient level (eg, lack of perception of risk), and health care provider level (eg, insufficient expertise in travel health). 4,5 Other possible explanations for why so few children are reached by preventive travel medicine efforts may be that specialized travel clinics are not prepared to provide services to children and/or that pediatric health care providers are not sufficiently trained in travel medicine. This issue warrants further study.…”
Section: Figurementioning
confidence: 99%
“…2 Tourism is the major reason for travel but, as a result of growing global migration, children often accompany caregivers on trips visiting friends and relatives (VFR) abroad. [3][4][5] Although children represent a significant proportion of the traveling public, little information is available regarding health problems of children traveling internationally. Most published literature on pediatric travel-related morbidity originated from singlecenter studies that reported only on hospitalized patients or focused on specific diseases (eg, malaria).…”
mentioning
confidence: 99%
“…En nuestro estudio encontramos que 42,2% de los turistas tuvo una CPV, siendo una cifra comparable a la de otro estudio piloto de 600 viajeros, donde se alcanzó a 52% 16 . Este hallazgo puede estar relacionado a la existencia de barreras para tener una CPV, como las consideraciones financieras, barreras del lenguaje, creencias de salud, falta de interés por el cuidado propio, el miedo a las autoridades de migración, entre otras 1 . En el análisis multivariado se encontró que los hombres tienen menor frecuencia de CPV, lo cual es respaldado por otros estudios 9 .…”
Section: Discussionunclassified